Shelf Life of Blackberry Fruits (Rubus fruticosus) with Edible Coatings Based on Candelilla Wax and Guar Gum - Alessandrina Ascencio-Arteaga; Silvia Luna-Suárez; Jeanette G. Cárdenas-Valdovinos; Ernesto Oregel-Zamudio; Guadalupe Oyoque-Salcedo; José A. Ceja-Díaz; María V. Angoa-Pérez; Hortencia G. Mena-Violante (Horticulturae, 2022)
Blackberries are very perishable with a limited shelf life due to a high metabolic activity and susceptibility to mechanical damage and microbial attack. The effect of edible coatings (EC) based on candelilla wax (CW) and guar gum (GG) on the quality, shelf life, bioactive-compounds content and antioxidant activity of blackberries stored at 25 ± 2 °C for 6 days, was evaluated. All EC contained GG (0.4%) and gallic acid (GA)(0.06%); EC1 contained CW (0.2%), glycerol (GL)(0.2%); EC2 contained CW (0.4%) and GL (0.2%); EC3 contained CW (0.2%) and GL (0.3%) and EC4 contained CW (0.4%) and GL (0.3%). The decay percentage (Decay%), physiological weight loss (%PWL), firmness, pH, total soluble solids (TSS), titratable acidity (TA), total phenolic content (TPC), total anthocyanin content (TAC) and antioxidant activity were analyzed. EC3 showed potential for prolonging the shelf life of blackberry by reducing Decay% (47%) and %PWL (64%) on day 6, while 86% of uncoated blackberries were decayed on day 4. Fruit coated with EC3 maintained pH, gradually reduced firmness, increased the TSS and decreased the TA. In addition, EC3 maintained the TAC and decreased the TPC in blackberries, while preventing a rapid increase in antioxidant capacity. Thus, EC3 showed to be a promising alternative in prolonging shelf life and preserving the quality of blackberries.